BIOMONITORING PENCEMARAN AIR MENGGUNAKAN IKAN SAPU-SAPU (Hypostomus Plecostomus) - Fitriani; Laorah Istifadilah; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Water pollution is an environmental problem caused by domestic, industrial, and agricultural activities that can degrade water quality and disrupt aquatic ecosystems. One method to assess water quality is biomonitoring using bioindicator organisms. Suckermouth catfish (Hypostomus plecostomus) is known for its high tolerance to polluted environments, making it a potential bioindicator of water pollution. This study aims to analyze the role and mechanism of suckermouth catfish as a bioindicator in aquatic ecosystems. The method used is a literature review based on various national and international scientific sources. The results show that suckermouth catfish respond to pollution through physiological changes, organ damage, behavioral alterations, and the accumulation of heavy metals in their body tissues. These responses indicate that the species can be effectively used to assess water quality.